Comparison of the size of bilateral testis in children with unilateral non-communicating hydrocele and its correlation with age. - Peiqiang Li; Fuyun Liu; Yan Huang (PLoS ONE, 2023)
Background Opinions on the optimal age for surgical management of hydroceles in young boys are not uniform. Scrotal ultrasonography can be used to diagnose hydroceles and measure testicular size. A comparison of bilateral testicular size with hydrocele and the change in trend with age has not been reported. We therefore aimed to analyze the bilateral testicular size of children with unilateral non-communicating hydroceles and examine the correlation between age and testicular volume. Methods Non-communicating hydrocele cases in children were included. Ultrasound results, age, and diagnose time were retrospectively recorded. The bilateral testicular size was compared, and the correlation between age and testicular volume was analyzed. Results There were 138 cases of non-communicating hydrocele, ranging in age from 11 to 72 months. The diagnose time ranged from 3 days to 54 months. The volume of the testis on the side of the hydrocele was larger than that on the normal side (P < 0.001). Testicular length was not different bilaterally. Testicular width and height were greater on the hydrocele side than on the normal testicular side (P<0.001). Age was positively correlated with testicular volume on the normal side (P = 0.004) but not on the hydrocele side. Conclusions An important finding was that when the contralateral normal testicular volume increases with age, the testicular volume does not increase on the hydrocele side. This finding confirms the adverse effects of hydrocele on testicular growth and provides a basis for early treatment.